Mortality Among Hardmetal Production Workers: A Retrospective Cohort Study in the Austrian Hardmetal Industry. Issue 12 (December 2017) - Wallner, Peter; Kundi, Michael; Moshammer, Hanns; Zimmerman, Sarah D.; Buchanich, Jeanine M.; Marsh, Gary M.
Abstract : Objective: This study retrospectively investigates causes of death among workers of a hardmetal plant in Austria. Methods: A retrospective cohort was formed of 1965 workers still employed in or after 1970. Follow-up was until end of 2014 based on national databases. Cobalt exposure was assessed through industrial hygiene data and urine analyses. Cox proportional hazards models were calculated for selected causes of death. Results: During 45, 598 years of observation in total 177 deaths were observed. Forty-nine workers died from any cancer, 10 from lung cancer, and three from chronic obstructive pulmonary disease. Only the latter showed a significant association with cumulative exposure. Conclusions: Although this is a young study population with little power to detect subtle effects, at least it does not indicate a pronounced cancer risk among tungsten carbide workers due to cobalt.